A FPGA Modeling Method for Power Electronic Topology Simulation - LIU Li; XU Lien; CHEN Liusong (Kongzhi Yu Xinxi Jishu)
Power electronic system has many switching devices and its mathematical model is complex and hard to analysis. In addition, the cycle of FPGA modeling is long. This paper proposed a FPGA rapid modeling approach for power electronic topology simulation. Firstly, a simplified mathematical model is obtained by the switch equivalent of power electronic switching devices, which helps to simplify the complicated mathematical analysis; secondly, power-analyze function is adopted to obtained system matrix; finally, according to the matrix of the system obtained, new FPGA model will be built easily and quickly, which can shorten 1/4 development time of FPGA. The simulation results demonstrate the effectiveness of the proposed method compared with the SimPowerSytem model.